Effect of Low-Molecular-Weight Organic Acids on Migration Characteristics of Pb in Reclaimed Soil - Zheng, Yonghong; Li, Yating; Zhang, Zhiguo; Tan, Yuning; Cai, Weiqing; Ma, Chengnan; Chen, Fangling; Lu, Jiangwei (Frontiers in Chemistry, 2022)
The effect of low molecular weight organic acids (citric acid and malic acid) on the migration characteristics of Pb in contaminated soils was explored in the present study. Reclaimed soil was collected from the coal gangue hill area of the Panyi Mine in Huainan city (China). The effect of citric acid and malic acid on the form of Pb present in the reclaimed soil was analyzed by spiking soil samples and simulating Pb contaminated soil. The results indicate that: (1) with increased concentration of exogenous Pb, the activity of Pb in the reclaimed soil was effectively improved. (2) the addition of citric acid and malic acid both resulted in increased fraction of exchangeable Pb in the soil, which effectively promoted the active Pb fraction. As the concentration of citric acid and malic acid increased, the active Pb fraction of the reclaimed soil increased accordingly. The Pb activation effect of citric acid was observed to be greater than that of malic acid. (3) with extended aging time, the activation effect of organic acids on Pb became weakened, with the loosely-bound Pb gradually transforming into strongly-bound Pb. Therefore, adding citric acid can be considered as a strategy to enhance the efficiency of reclaimed soil remediation due to the ability of Pb activation.